Ultrasonication-Assisted Preparation of Virgin Coconut Oil-Kelulut Honey-Vitamin E Emulsion and Its Bioactivity for Lip Balm Application - Nur Safiah Esrifadli; Sity Aishah Mansur; Angzzas Sari Mohd. Kassim; Noor Akhmazillah Mohd. Fauzi; Aliff Hisyam A Razak; Mohhar Mohammed (Journal of Advanced Industrial Technology and Application, 2025)
The growing demand for natural and eco-friendly skincare products has spurred innovation in cosmeceutical formulations, including lip balms. This study developed an emulsion-based lip balm incorporating Virgin Coconut Oil, Kelulut honey, and vitamin E, utilizing ultrasonication to enhance stability and bioactivity. The moisturizing, antibacterial, and antioxidant properties of these ingredients were combined with surfactants (Tween 20, soy lecithin, or a 50:50 blend) and processed through ultrasonication and/or homogenization. Bioactivity was assessed using pH, Total Phenolic Content (TPC), Total Flavonoid Content (TFC), 2,2-Diphenyl-1-Picrylhydrazyl (DPPH), and Ferric Reducing Antioxidant Power (FRAP) assays. Sample F (50:50 blend with ultrasonication) demonstrated the highest TPC (38.95 µg GAE/mL), TFC (5.59 µg QE/mL), DPPH inhibition (17.14%), and FRAP activity (2.68 µg GAE/mL), with a skin-compatible pH (4.80–5.50). The storage stability test conducted at 4°C for one week revealed visible phase separation in all samples, with samples B, D, and F (with ultrasonication) demonstrating comparatively less separation than their respective counterparts A, C, and E, (homogenization only) indicating enhanced emulsion stability under chilled conditions. Sensory evaluation identified Sample F as the most preferred, excelling in texture, spreadability, and absorption. This study underscores the significance of ultrasonication, surfactant synergy, and ingredient selection in developing sustainable, high-performance cosmeceutical formulations.